PENERAPAN DIFERENSIASI KONTEN DALAM LKPD MENGGUNAKAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT) PADA PEMBELAJARAN BAHASA INDONESIA - Rahmawati, Fitri Rizki; Suhardi, Suhardi (STAI Sangatta Kutai Timur, 2024)
This study aims to analyze students' interest in learning Indonesian through the application of content differentiation tailored to the Culturally Responsive Teaching (CRT) approach in the eighth grade at SMP Negeri 7 Tanjungpinang. This classroom action research was conducted in two cycles, where data were collected through questionnaires and observations. The results indicate that the application of content differentiation based on local culture successfully improved students' interest and understanding of the taught material. The average interest score of students reached 4.3 for culturally relevant material, showing an increase in motivation (4.1), active engagement (4.0), and understanding of the material (4.2). These findings suggest that the CRT approach can enhance engagement and the relevance of learning, creating a more inclusive learning environment. This study provides important implications for developing a curriculum that is more responsive to students' cultural needs and characteristics, and recommends the implementation of adaptive teaching strategies to achieve better learning outcomes.